Human Capital Development of Information and Communication Technology Industry in Indonesia - Hani Gita Ayuningtias; Grisna Anggadwita (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2015)
Industri teknologi informasi dan komunikasi (TIK) memainkan peran utama dalam transisi pengetahuan berbasis ekonomi, dan berpeluang untuk pembangunan sosial-ekonomi, terutama bagi negara-negara berkembang. Human capital memainkan peran penting dalam sektor berbasis pengetahuan seperti industri TIK. Di negara berkembang khususnya Indonesia, human capital merupakan faktor pendorong penting pertumbuhan industri TIK. Sehingga, perusahaan harus menginvestasikan sumber daya yang diperlukan dalam mengembangkan sumber daya manusia yang cenderung memiliki dampak yang besar pada kinerja. Artikel ini menjelaskan dan menganalisis peran modal manusia dalam pengembangan industri TIK di Indonesia serta mengembangkan model berdasarkan rangkuman teori yang telah ada yang menjelaskan hubungan antara pengembangan modal manusia dan kinerja perusahaan ICT. Model yang dikembangkan diharapkan dapat menjadi acuan dalam pengembangan human capital di industri lainnya, khususnya di negara berkembang. Abstract The industry of information and communication technology (ICT) has an important role in the transition of economic-based knowledge, and has a chance in the social-economic development, particularly for the developing countries. Human capital is indeed important in the knowledge- based sector like IT industry. In developing countries, particularly Indonesia, human capital was the strongest factor to stimulate the growth of IT industry. Human capital is intangible asset which is very important to be developed. Therefore, companies must invest their capital to develop their human capital which tends to give a high impact on companies’ performance. This paper explained and analyzed the role of human capital in term of ICT industry development in Indonesia, then developed the model by summarizing existing theories that explained the relationship between development of human capital and the performance of ICT companies. The model that developed was expected to be the benchmark for human capital development in the other industries, particularly in developing country.